Assessing neo-natal mortality trends in Pakistan: an insight using equity lens - Zainab Dawood; Naeem Majeed (BMC, 2022)
Abstract Background Almost 2.5 million neonates died in the first year of life in the year 2017. These account for almost half of the total deaths of children under the age of 5 years. Overall, child mortality has declined over the past two decades. Comparatively, the pace of decline in neonatal mortality has remained much slow. Significant inequalities in health across several dimensions - including wealth, ethnicity, and geography - continue to exist both between and within countries, and these contribute to neonatal mortality. This study aims to quantify the magnitude of inequalities in neonatal mortality trends by wealth quintile and place of residence with province wise segregation. Methods The study was done using raw data from the last three Pakistan Demographic & Health Surveys (2017-18, 2012-13 and 2006-07). The concentration curves were drawn in Microsoft Excel 365 using scatter plot as graph type while the frequencies were calculated using SPSS 24. Results The situation of inequity across provinces and in rural vs urban areas has slightly declined, however, gross inequities continue to exist. Conclusions Presentation of outcomes data, such as neonatal mortality in various wealth quintiles is an effective way to highlight the inequities amongst income groups as it highlights the vulnerable and at-risk groups. In other countries, rural-urban distribution, or ethnic groups may also reflect similar differences and help in identifying high-risk groups.